2017
DOI: 10.1021/acs.joc.6b02816
|View full text |Cite
|
Sign up to set email alerts
|

Formal Total Synthesis of Manzacidin C Based on Asymmetric 1,3-Dipolar Cycloaddition of Azomethine Imines

Abstract: An enantioselective formal total synthesis of (+)-manzacidin C is described. A key feature of the synthesis is the construction of two chiral centers via the asymmetric 1,3-dipolar cycloaddition of an azomethine imine to methallyl alcohol by the use of (S,S)-DIPT as a chiral auxiliary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Conversion of 22 to manzacidin C is well-documented in the literature, proceeding in two facile steps . Overall, our approach constitutes a five-step formal synthesis of manzacidin C, and compares favorably to previous approaches to this alkaloid . More importantly, we showed that incorporation of enzymatic methods into the precepts of C–H functionalization logic can dramatically simplify a synthesis design.…”
Section: Resultsmentioning
confidence: 57%
“…Conversion of 22 to manzacidin C is well-documented in the literature, proceeding in two facile steps . Overall, our approach constitutes a five-step formal synthesis of manzacidin C, and compares favorably to previous approaches to this alkaloid . More importantly, we showed that incorporation of enzymatic methods into the precepts of C–H functionalization logic can dramatically simplify a synthesis design.…”
Section: Resultsmentioning
confidence: 57%
“…A telescoped hydrogenation/dual Boc protection/selective lactonization procedure then afforded lactone 10 in 41% yield over two steps (Figure B). Given the aforementioned two-step elaboration of 10 to the natural product, our route represents a five-step formal synthesis of manzacidin C and a drastic improvement in step economy over prior approaches . This improvement, coupled with absolute regio- and stereocontrol, underscores the capability of enzymatic C–H functionalization to streamline synthetic efforts.…”
Section: Amino Acid Functionalizationmentioning
confidence: 96%
“…The versatile reactivities of N,N -cyclic azomethine imines have been consistently explored, allowing the facile construction of a variety of dinitrogen-fused heterocyclic systems. Thus, owing to their inherent dipolar character, a range of dipolarophiles including olefins [11], alkynes [12], enones [13], isocyanides [14], and allenes [15] were subjected to [3 + n] dipolar cyclization with N,N -cyclic azomethine imines to derive a range of fused dinitrogen-containing heterocycles. Interestingly, dimerization of N,N -cyclic azomethine imine under the UV-irradiation was observed by Rodina and Geissler et al, leading to the formation of a 1,5-diazabicycle [16,17].…”
Section: Introductionmentioning
confidence: 99%